Effect of Porang (Amorphophallus muelleri Blume) Flour Diet on Postprandial Blood Sugar Rates and Insulin Resistance in Male Wistar Rats (Rattus norvegicus) Diabetes Mellitus - Nathasia; Widhiartini, Ida Ayu Alit; Dwipayana, I Made Pande; Wahyuni, Nila; Maratni, Ni Putu Tesi; Hendrayana, Made Agus (HAYATI Journal of Biosciences, 2026)
Medical nutrition therapy is essential in diabetes management, especially as diabetes is often linked with aging. Porang tuber flour contains glucomannan, a compound with potential glucose-lowering effects. This study aimed to evaluate the effect of porang flour feeding frequency on 2-hour postprandial blood glucose (2hPPBG) and HOMA-IR in diabetic rats. Using a quasi-experimental pre-test and post-test control group design, 21 male Wistar rats were induced with diabetes via streptozotocin and nicotinamide, then randomly assigned to three groups: G0 (control, given aquadest), G1 (porang flour 300 mg/kg BW daily), and G2 (porang flour 300 mg/kg BW every two days). Five rats died during treatment. Wilcoxon test results showed a difference in 2hPPBG levels between each group before and after treatment. There was no decrease in G0 (p = 0.893), but a decrease in G1 (p = 0.043) and G2 (p = 0.028). The difference between HOMA-IR before and after treatment did not decrease in groups G0 (p = 0.345), G1 (p = 0.138), and G2 (p = 0.249). Post hoc test for 2hPPBG levels between groups showed a significant difference between G0 and G1 (p<0.001), a significant difference between G0 and G2 (p<0.001), and no significant difference between G1 and G2 (p = 0.135). One-way ANOVA test of HOMA-IR showed no significant difference between G0, G1, and G2 (p = 0.148). It was concluded that porang flour can reduce 2hPPBG, but not HOMA-IR. There was no difference in 2hPPBG levels between administering porang flour daily and every other day.